Respon bayam brazil (Althernanthera sissoo) dengan beda sifat kimia tanah dan panjang stek batang - Aldi Prasetyo; Aulia Rahmawati (Fakultas Pertanian Universitas Majalengka, 2025)
Brazilian spinach is a type of vegetable that can be harvested in a relatively short time and has economic value. This plant can be used as food coloring, ground cover plants and as ornamental plants, so it has the potential to be cultivated. This study aims to determine the effect of soil chemical properties and stem cuttings length on the growth and yield of Brazilian Spinach. The method used in this research is a complete group randomized design with two factors, namely soil collection point 1, soil collection point 2, soil collection point 3 with different soil chemical properties and the second factor is the length of stem cuttings (5 cm, 10 cm, and 15 cm). The results of this study showed that the factor of soil collection point (M) did not have a significant effect on the growth and yield of Brazilian spinach. While the stem cuttings length factor gave significant results. Of the various weight parameters showed the best results in the 15 cm length treatment (P3).